Perancangan Aplikasi Sistem Informasi Keuangan Berbasis Web: Studi Kasus di Lembaga Keuangan Mikro Syariah Al-Falah POLBAN - Qornan Al-Izzatul 'Ulya; Ine Mayasari; Hamdani Arifulsyah; Heri Ribut Yuliantoro (Journal of Applied Islamic Economics and Finance, 2022)
The purpose of this research is to produce an accounting information system application that will provide information related to member data, savings data and recording of savings and loan transactions at the Al-Falah Polban Syariah Microfinance Institution. Other goals include making it easier to record financial transactions, presenting reports on cash deposits, cash withdrawals, member data, savings data, and general journals at the Al-Falah Polban Sharia Microfinance Institution. And find out whether the application of this research can help the company's performance to be better and more efficient or not. This research methodology uses research and development (R&D) methods, namely processes or steps that develop new products or improve existing products that can be accounted for. According to other sources, research and development methods are research methods used to make certain products and test the effectiveness of those products. The product in question can be in the form of software or computer programs, as well as hardware, such as tools, books, modules, or other equipment. The results of the questionnaire distributed to users, this LKMS information system application is included in the very good category, which means that by using this application, recording financial data, making savings and loan transaction reports, member data, savings data, and general journals is faster and more accurate.